Impact of nitrogen management and nano-urea on yield, quality and storage attributes of garlic (Allium sativum) - CHOUDHARY, RAJESH; CHOUDHARY, M R; CHOUDHARY, ANITA; SHARMA, YOGESH KUMAR; CHOUDHARY, ASHOK; DOODHAWAL, KIRAN; YADAV, D K; JAT, S K; MANDAL, NEELUM KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during winter (rabi) seasons of 2020–21 and 2021–22 at Sri Karan Narendra College of Agriculture, Jobner, Jaipur, Rajasthan to evaluate the impact of nitrogen management (organic and inorganic sources), biofertilizer and foliar spraying of nano-urea on yield, quality and storage attributes of garlic (Allium sativum L.). The experiment consisted of 3 levels of organic and inorganic fertilization, 2 levels of bio-fertilizers in main plot, and 4 levels of nano-urea arranged in split plot design (SPD) in sub plot. The results showed that yield, quality and storage attributes of garlic, viz. number of cloves/bulb (16.46%), clove length and girth, average weight of clove (1.56 gm), nitrogen, phosphorus and potassium content in bulb (1.10, 0.31 and 0.51%), physiological loss in weight, shelf-life of bulbs and rooting percentage of bulbs were significantly enhanced by 100% recommended dose of nitrogen through inorganic fertilizers and bio-fertilizer in main plot. In sub plot, the foliar spray of nano-urea @75 ml/ha recorded highest number of cloves per bulb (16.26%), clove length and girth (2.86 and 1.07 cm), average weight of clove (1.55 gm), nitrogen, phosphorus and potassium content in bulb (1.09, 0.31 and 0.51%), shelf-life of bulbs and rooting percentage of bulbs. Therefore, this study concluded that the nitrogen management and nano-urea in garlic crop gives better yield, quality and storage attributes, and can be opted in semi-arid climatic conditions.